Biceps Tenodesis versus Allograft Reconstruction for Varus Instability - Beiro, Cristobal; Parks, Brent G.; Tsai, Michael; Hinton, Richard Y. (The Journal of Knee Surgery, 2014)
Although effective to restore stability in varus laxity, a fibula-based procedure such as figure-of-8 reconstruction can be technically demanding and requires use of allograft or autograft. Biceps rerouting offers an alternative without the potential complications of allograft or autograft procedures. It is not known whether biceps tenodesis is effective in addressing isolated varus laxity with lateral collateral ligament (LCL) rupture. We compared biceps tenodesis and figure-of-8 allograft reconstruction for restoration of varus stability. Nine knees were loaded at 10 N-m at 0- and 30-degree knee flexion in intact, LCL sectioned, and reconstructed state. Both biceps tenodesis and figure-of-8 reconstruction restored varus stability to at least baseline stability. Normalized displacement with biceps tenodesis measured at time zero was significantly lower than with allograft reconstruction at 0 degrees (0.75 ± 0.26 vs. 1.09 ± 0.31 degrees; p = 0.04) and 30 degrees (0.66 ± 0.14 vs. 0.91 ± 0.27 degrees; p = 0.04). Biceps tenodesis was effective at restoring baseline varus stability in isolated varus laxity.
Keywords: varus laxity; knee ligamentous reconstruction; biomechanics; knee; primary knee restraints